Seni Tradisi Nusantara Gondang Buhun Sebagai Media Pendidikan Karakter Remaja di Kabupaten Pangandaran - Nia Emilda; Ai Juju Rohaeni; Wanda Listiani (Jurnal Budaya Nusantara, 2017)
Pangandaran regency is one of the regencies in West Java province which has a diversity of art and culturethat is continuously maintained its sustainability. One of the art traditions is Gondang Buhun. It is a traditional artthat is maintained by the local community hereditary and has noble values that can be used as a medium of educationcharacters for adolescents in Pangandaran Regency. This research uses qualitative method with case study approachwhich describes the process of art of Gondang Buhun tradition as a medium of adolescent education characters. Theresult of this research is Gondang Buhun art process as a media of educational characters; The supporting andinhibiting factors of Gondang Buhun tradition are as media of educational characters; and educational efforts ofadolescent characters through the art of Gondang Buhun tradition.